Who should participate in health care priority setting and how should priorities be set? : evidence from a Portuguese survey - Veloso, Anabela Botelho (2020)
ABSTRACT - Introduction: This article provides highlights of the evolution of the health care rationing debate towards a more explicit and open approach involving public participation. Discretionary models that have dominated the health sector decision-making are being questioned by different sectors of society. Methods: Using data from 442 college students, we explore public views on public involvement in health care rationing decisions. Results: Findings suggest that although citizens wish to be consulted, they believe doctors should play the most important role on rationing decisions. Discussion: Confidence in doctors is, nonetheless, not independent from the criteria used to support their decisions.